A light alloy design method with complex component synergy
Through the entropy increase idea, the components of multi-component alloys were designed, and the combination of alloying elements was determined using thermodynamic mixed entropy value ΔSmix, which solved the problem of inefficient design of multi-component alloys in the prior art, and achieved the effect of efficient screening of optimal component combinations .
Patent Information
- Application Number
- CN202210204322.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-03-02
- Publication Date
- 2025-02-07
- Estimated Expiration
- 2042-03-02
AI Technical Summary
The existing phase diagrams of aluminum alloys and magnesium alloys are mainly binary or small ternary, making it difficult to design high-performance multicomponent alloys. The exploration of the composition of existing multicomponent alloys mostly depends on the 'trial and error method', resulting in low efficiency. and high cost.
The composition of multi-component alloys is designed using the idea of entropy increase, and the combination of alloying elements is determined by mixing the entropy value ΔSmix through thermodynamic mixing, and preliminary design is carried out according to the principle of proportioning between medium-entropy alloys and high-entropy alloys, and casting and hot extrusion are carried out through smelting. Alloys are prepared by deformation and other processes, and finally the optimal component combination is determined through mechanical properties testing.
It improves the screening efficiency of multi-alloys, simplifies the design process, can quickly screen out the optimal composition ratio within a larger element range, and the preparation process is relatively simple.
Smart Images

Figure CN114582444B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of light alloy material design and preparation, and mainly relates to a light alloy design method with synergistic effects of complex components. Background Art
[0002] Green and energy-saving are the development trends of the current materials industry. Aluminum and magnesium, as lightweight metals, have become the most promising materials in the 21st century due to their low density, high specific strength and excellent heat dissipation performance. However, with the iteration and update of the materials industry, the market has also put forward higher requirements for the performance of materials. The development of high-performance lightweight aluminum alloys and magnesium alloys is necessary to achieve their large-scale application and promote the development of new materials. From the development history of materials, the design of alloy composition mainly relies on phase diagrams, but the existing aluminum alloy and magnesium alloy phase diagrams are basically binary phase diagrams and a small number of ternary phase diagrams, and the quaternary and above phase diagrams are basically blank. In recent years, in the development process of new high-performance aluminum alloys and magnesium alloys, a trend of diversified composition has gradually emerged. By adding a variety of small amounts of alloying elements, they can play different roles and synergistically improve the mechanical properties of the alloy, showing obvious advantages. This leads to great limitations in the design of multi-component alloy compositions by alloy phase diagrams. Most of the existing explorations of the composition of multi-component alloys adopt the "trial and error method", that is, adding alloy elements one by one from low to high to determine the optimal addition amount of the element. Although this method has a certain degree of universality, as the number of alloying elements increases, the possible composition combinations also increase, which will bring great time and economic losses, and it is difficult to obtain the optimal composition combination. Therefore, it is necessary to study a design and preparation method for multi-component alloys to address the shortcomings of existing alloy design methods, so as to solve or alleviate the above-mentioned problems in multi-component alloy composition design. Summary of the invention
[0003] In order to solve the problems existing in the prior art, the present invention provides a light alloy design method with complex component synergy, which provides a composition design concept of multi-component alloys based on entropy increase, which can improve the screening efficiency of alloys and is not limited by the number of alloying elements. The light alloys with preliminary design are prepared by ordinary smelting and casting process, or ordinary smelting and casting process and one-time hot extrusion deformation, and then tested to determine the one with the best performance, which is the target light alloy of the final design.
[0004] In order to achieve the above object, the present invention adopts the following technical solutions:
[0005] A light alloy design method for complex component synergy of the present invention comprises the following steps:
[0006] Step 1: Preliminary Design
[0007] S1: Select the target alloying elements according to the performance requirements of the light alloy to be designed, and the number of target alloying elements is ≥4;
[0008] S2: The selected target alloying elements are combined according to the medium entropy alloy ratio principle and the high entropy alloy ratio principle in which the system mixing entropy value ΔSmix is greater than or equal to 1R in thermodynamics, so as to obtain an alloying element combination that meets the medium entropy alloy and high entropy alloy ratio principles;
[0009] in, ΔS mix is the mixing entropy value, the unit is J / (k·mol), R is the gas constant (=8.314 J / (k·mol)), n is the number of elements, c i is the atomic percentage of the corresponding element;
[0010] Furthermore, the ratio principle of medium entropy alloy is: 1R≤ΔS mix ≤1.5R;
[0011] The principle of high entropy alloy ratio is: ΔS mix >1.5R.
[0012] In the alloying element combination that complies with the ratio principle of medium entropy alloy and high entropy alloy, the atomic percentage range of each alloying element is 5-35%.
[0013] S3: Adding alloying elements that meet the ratio principle of medium-entropy alloy and high-entropy alloy into the base material in increasing amounts to obtain a light alloy with multiple groups of complex components that are preliminarily designed to work together;
[0014] Furthermore, the matrix material is preferably aluminum or magnesium.
[0015] Step 2: Preparation
[0016] According to the elements and element contents in the light alloy of the complex components synergistically designed in the above-mentioned multiple groups, the raw materials are weighed, smelted and cast to obtain alloy ingots;
[0017] In the step 2, the raw materials need to be dried before smelting, the drying temperature is 100-200° C., and the drying time is 30-60 minutes.
[0018] The smelting temperature is the temperature of the matrix ingot melting point + (50-80)°C.
[0019] In the step 2, the base material is first added to the smelting, and then the alloying element combination that conforms to the ratio principle of medium entropy alloy and high entropy alloy is added. According to the state of the alloying elements after the previous combination, the addition is divided into two ways:
[0020] The first method is to prepare an ingot with a combination of alloying elements that conforms to the ratio principle of medium-entropy alloy and high-entropy alloy, and then add the ingot to the matrix material in increasing amounts;
[0021] The second method is to directly add the designed element components into the matrix material in the form of an intermediate alloy or pure metal according to the designed mass percentage of each element, and adjust the addition temperature and addition order according to the melting point of the alloy element.
[0022] In the step 2, during smelting and casting, slag removal, refining, slag-metal separation, casting and homogenization heat treatment processes are also required.
[0023] Specifically, remove the slag on the surface of the melt, add refining agent while stirring, and continue refining for 5 to 10 minutes. Then let it stand for 15 to 30 minutes to fully separate the impurities and the alloy melt;
[0024] When the temperature of the alloy melt is 50 to 80°C above the melting point, the slag on the surface of the melt is removed and the melt is cast into a mold. After cooling to room temperature, the ingot is taken out and an inert gas is used for protection during the casting process.
[0025] The homogenization heat treatment is carried out at 350-550° C. for 8-24 hours.
[0026] The step 2 may further include subjecting the alloy ingot to hot extrusion deformation to obtain a deformed sample;
[0027] More preferably, the temperature of the hot extrusion deformation is 200 to 400° C., the extrusion speed of the hot extrusion deformation is 0.1 to 5 mm / s, the hot extrusion deformation is preferably a single-pass hot extrusion deformation, and after the hot extrusion deformation, air cooling to room temperature is performed.
[0028] Step 3: Testing
[0029] The alloy ingots or deformed samples are subjected to mechanical property tests, and the final mechanical properties of light alloys with synergistic effects of multiple groups of initially designed complex components are compared to obtain the light alloy component combination corresponding to the optimal performance.
[0030] In the step three, the mechanical properties include strength and elongation.
[0031] The main features of the light alloy design method with complex component synergy of the present invention are:
[0032] Compared with the existing multi-component alloy design method, the design method of the present invention can improve the screening efficiency of multi-component alloys and is not limited by the number of alloy components. It is simple and efficient, can quickly screen out the optimal composition ratio within a larger element range, and has a simple preparation process.
[0033] The present invention can also determine the composition combination corresponding to the optimal performance by performing hot extrusion deformation or not, according to the variation trend of alloy properties with the addition of alloy elements, and guided by mechanical properties (strength and elongation). BRIEF DESCRIPTION OF THE DRAWINGS
[0034] In order to explain the design scheme and preparation method of the multi-component alloy of the present invention in more detail, the following briefly introduces the drawings required for use in the embodiments or the description of the prior art;
[0035] Figure 1 It is a schematic flow chart of a design method of a light alloy with complex components acting synergistically provided by the present invention;
[0036] Figure 2 is a trend diagram of mechanical properties of a multi-component magnesium alloy after hot extrusion deformation prepared in Example 1 of the present invention;
[0037] Figure 3 This is a trend diagram of the mechanical properties of the multi-component magnesium alloy prepared in Example 1 of the present invention without hot extrusion deformation. DETAILED DESCRIPTION
[0038] In order to more clearly explain the design method of the light alloy with multiple groups of complex components in the present invention, the method of the present invention is described in detail below in conjunction with the embodiments. The following is a basic description of the concept of the present invention.
[0039] Embodiment 1:
[0040] A design method for a light alloy with complex component synergy, the flow diagram of which is shown in Figure 1 , including the following steps:
[0041] Based on the requirement of preparing low-cost high-performance magnesium alloy, the target alloying elements are determined to be: Al, Ca, Mn, Zn, Sn, and the matrix material is pure magnesium. Then, according to the high entropy alloy ratio principle, these five alloying elements are mixed in an equiatomic ratio, namely: Al 20 Ca 20 Mn 20 Zn 20 Sn 20 , whose mixing entropy is ΔS mix =-ln0.2 = 1.6R;
[0042] Design Al from low to high principle 20 Ca 20 Mn 20 Zn 20 Sn 20The addition amount is initially designed to be 1wt.%, 3wt.%, 5wt.%, 7wt.%, and the base material is commercial pure magnesium. The corresponding alloy codes are AXMZT-1, AXMZT-3, AXMZT-5, and AXMZT-7. Since the added target alloying elements can react with magnesium melt, the designed Al 20 Ca 20 Mn 20 Zn 20 Sn 20 The addition amount of each is converted into the addition value of the corresponding pure metal or master alloy. Then the target alloy ingot is prepared by ordinary smelting and casting method. Among them, Al, Zn, Sn are added by commercial pure metal ingots, Ca is added by Mg-Ca master alloy, and Mn is added by anhydrous MnCl2 particles;
[0043] Table 1 Chemical composition of the multi-component magnesium alloy prepared by the design method provided in Example 1 of the present invention;
[0044]
[0045] The prepared raw materials are dried at 200°C for 30 minutes, and then the pure magnesium ingot is placed in an iron crucible, and the surface is evenly sprinkled with No. 2 magnesium alloy special flux, and then placed in a resistance furnace and heated to 710±10°C. After the magnesium ingot is completely melted, the melt is cooled to 680°C, and the dried Al, Zn, and Sn ingots are added, and the temperature is kept at this temperature for 5 minutes and stirred for 5 to 10 minutes. After stirring, No. 2 flux is sprinkled on the surface of the melt;
[0046] Heat the melt to 730℃, remove the oxide slag on the melt surface and add anhydrous MnCl2, use a slag scoop to gently press the anhydrous MnCl2 into the melt, keep it at this temperature for 5 minutes and stir it for 5 to 10 minutes, and sprinkle No. 2 flux on the melt surface after stirring;
[0047] After the melt temperature is lowered to 680°C, the oxide slag on the melt surface is removed and the Mg-Ca master alloy is added. The melt is kept at this temperature for 5 minutes and then stirred for 5 to 10 minutes.
[0048] After all ingredients are added, remove the slag on the surface of the melt, add No. 2 flux while stirring for refining, the duration is 5 to 10 minutes. Then the melt is left to stand at 700℃ for 15 minutes to allow the impurities and melt to be fully separated;
[0049] After the melt temperature is raised to 710-720°C, the oxidized slag on the melt surface is removed, and the melt is cast into a mold. After cooling to room temperature, the alloy ingot is taken out. During the casting process, a mixed gas of CO2+SF6 with a volume ratio of 99:1 is used for protection;
[0050] The alloy ingot was subjected to homogenization heat treatment in a resistance furnace at a temperature of 350°C for 5 h and 500°C for 10 h.
[0051] The homogenized ingot is machined into an extruded ingot with a height of 100 mm and a diameter of 46-48 mm, and then subjected to a single-pass hot extrusion deformation at a hot extrusion deformation temperature of 300°C and an extrusion speed of 0.8-1 mm / s. The extruded bar is air-cooled;
[0052] The mechanical properties of the alloys before and after hot extrusion deformation were tested and their trend diagrams were drawn. Figure 2 and Figure 3 , the best performance component combination was selected based on strength and elongation as Mg-5wt.%Al 20 Ca 20 Mn 20 Zn 20 Sn 20 .
[0053] Embodiment 2:
[0054] A design method for a light alloy with complex component synergy is the same as that in Example 1, except that:
[0055] The composition and preparation of alloy ingots are different, specifically as follows:
[0056] (1) Based on the requirements of low cost, low density and high performance, the target alloying elements are determined as: Al, Ca, Mn, Zn, Li. According to the high entropy alloy ratio principle, these five elements are mixed in an equiatomic ratio, namely: Al 20 Ca 20 Mn 20 Zn 20 Li 20 , whose mixing entropy is ΔS mix =-ln0.2 = 1.6R;
[0057] (2) Li is added in the form of high-purity Li strips at a temperature of 680°C;
[0058] (3) The mechanical properties of the alloys before and after hot extrusion deformation were tested. The optimal composition was selected based on strength and elongation as Mg-5wt.%Ca 20 Mn 20 Zn 20 Sn 20 Li 20 .
[0059] Embodiment 3:
[0060] A design method for a light alloy with complex component synergy is the same as that in Example 1, except that:
[0061] The composition and preparation of alloy ingots are different, specifically as follows:
[0062] (1) The target alloying elements are Ca, Mn, Zn, Sn, and Li, and the selected matrix is pure aluminum. According to the high entropy alloy ratio principle, the atomic ratio is combined, that is, Ca 20 Mn 20 Zn 20 Sn 20 Li 20 , whose mixing entropy is ΔS mix =-ln0.2=1.6R; the designed addition amount is 1wt.%, 3wt.%, 5wt.%, 7wt.%. Because the added target alloying elements can react with aluminum melt, the designed Ca 20 Mn 20 Zn 20 Sn 20 Li 20 The addition amount of each element is converted into the corresponding addition value of pure metal or master alloy. Ca and Mn are added using Al-Ca and Al-Mn master alloys respectively. Zn, Sn, and Li are added using pure metal ingots;
[0063] (2) placing a dried pure aluminum ingot in a graphite crucible and heating it to 730±10° C., and after the pure aluminum ingot is completely melted, adding Al-Ca, Al-Mn, Zn, Sn and Li ingots in sequence to obtain an alloy melt;
[0064] (3) When the temperature is 730±10°C, hexachloroethane is added for refining for 30 minutes, and then the melt is allowed to stand for 30 minutes. When the melt temperature drops to 710±5°C, the slag on the surface of the melt is removed and the melt is cast into a mold preheated at 200°C to obtain the target alloy ingot;
[0065] (4) subjecting the prepared target alloy ingot to homogenization heat treatment in a resistance furnace at a temperature of 450° C. for 24 h and air cooling;
[0066] Then, hot extrusion deformation is performed, the temperature of hot extrusion deformation is 400°C, the extrusion speed of hot extrusion deformation is 4-5mm / s, and after hot extrusion deformation, air cooling is performed to room temperature;
[0067] (5) Mechanical properties of each alloy component were tested before and after hot extrusion. The optimal component combination was selected based on strength and elongation as Al-3wt.%Ca 20 Mn 20 Zn 20 Sn 20 Li20 .
[0068] Example 4
[0069] A design method for a light alloy with complex component synergy is the same as that in Example 1, except that:
[0070] The composition and preparation of alloy ingots are different, specifically as follows:
[0071] (1) The target alloying elements are Al, Ca, Zn, and Mn, and the selected matrix is pure magnesium. According to the ratio principle of medium entropy alloy, these four elements are mixed in equal atomic ratios, namely: Al 25 Ca 25 Mn 25 Zn 25 , whose mixing entropy is ΔS mix =-ln0.25=1.38R; the designed addition amount is 1wt.%, 3wt.%, 5wt.%, 7wt.%, 10wt.%. Because the added target alloying elements can react with the magnesium melt, the designed Al 25 Ca 25 Mn 25 Zn 25 The addition amounts of each element are converted into the corresponding addition values of pure metals or master alloys. Among them, Al and Zn are added using commercial pure metal ingots, Ca is added using Mg-Ca master alloy, and Mn is added using anhydrous MnCl2 particles;
[0072] (2) subjecting the prepared target alloy ingot to homogenization heat treatment in a resistance furnace at 400°C for 12 h and air cooling;
[0073] Then, a single-pass hot extrusion deformation is performed, the temperature of the hot extrusion deformation is 300°C, the extrusion speed of the hot extrusion deformation is 2-3 mm / s, and after the hot extrusion deformation, air cooling is performed to room temperature;
[0074] (5) The mechanical properties of the alloys before and after hot extrusion were tested. The optimal composition was selected based on strength and elongation as Mg-7wt.%Al 25 Ca 25 Mn 25 Zn 25 .
[0075] Example 5
[0076] A design method for a light alloy with complex component synergy is the same as that in Example 1, except that:
[0077] The composition and preparation of alloy ingots are different, specifically as follows:
[0078] (1) The target alloying elements are Mg, Ca, Zn, Mn, and Li, and the selected matrix is pure aluminum. According to the ratio principle of high entropy alloy, these five elements are mixed in an equiatomic ratio, namely: Mg 20 Ca 20 Zn 20 Mn 20 Li 20 , whose mixing entropy is ΔS mix =-ln0.2=1.6, and prepare Mg 20 Ca 20 Zn 20 Mn 20 Li 20 The high entropy alloy ingot is reserved; the designed addition amount is 1wt.%, 3wt.%, 5wt.%, 7wt.%, 10wt.%.
[0079] (2) Place the dried pure aluminum ingot in a graphite crucible and heat it to 730±10℃. After the pure aluminum ingot is completely melted, add Mg according to the designed addition amount. 20 Ca 20 Zn 20 Mn 20 Li 20 Casting high entropy alloy ingots to obtain alloy melts;
[0080] (3) When the temperature is 730±10°C, hexachloroethane is added for refining for 30 minutes, and then the melt is allowed to stand for 30 minutes. When the melt temperature drops to 710±5°C, the slag on the surface of the melt is removed and the melt is cast into a mold preheated at 200°C to obtain the target alloy ingot;
[0081] (4) subjecting the prepared target alloy ingot to homogenization heat treatment in a resistance furnace at a temperature of 420° C. for 24 h and air cooling;
[0082] Then, hot extrusion deformation is performed, the temperature of hot extrusion deformation is 350°C, the extrusion speed of hot extrusion deformation is 2-3 mm / s, and after hot extrusion deformation, air cooling is performed to room temperature;
[0083] (5) Mechanical properties of each alloy component were tested before and after hot extrusion. The optimal component combination was selected based on strength and elongation as Al-7wt.%Mg 20 Ca 20 Zn 20 Mn 20 Li 20 .
[0084] Example 6
[0085] A design method for a light alloy with complex component synergy is the same as that in Example 1, except that:
[0086] The composition and preparation of alloy ingots are different, specifically as follows:
[0087] (1) Based on the requirements of low density and high performance, the target alloying elements are determined as: Al, Ca, Mn, Zn, and Li. These five elements are combined according to the high entropy alloy ratio principle to form Al 10 Ca 20 Mn 20 Zn 20 Li 30 , whose mixing entropy is ΔS mix =-(0.1ln0.1+0.6ln0.2+0.3ln0.3)=1.55R, the matrix material is pure magnesium. 10 Ca 20 Mn 20 Zn 20 Li 30 The high entropy alloy ingot is reserved; the designed addition amount is 1wt.%, 3wt.%, 5wt.%, 7wt.%, 10wt.%.
[0088] (2) Place the dried pure magnesium ingot in an iron crucible and heat it to 710±10℃. After the magnesium ingot is completely melted, add Al 10 Ca 20 Mn 20 Zn 20 Li 30 Casting high entropy alloy ingots to obtain alloy melts;
[0089] (3) subjecting the prepared target alloy ingot to homogenization heat treatment in a resistance furnace at a temperature of 400°C for 10 h and air cooling;
[0090] Then, hot extrusion deformation is performed, the temperature of hot extrusion deformation is 350°C, the extrusion speed of hot extrusion deformation is 1-2 mm / s, and after hot extrusion deformation, air cooling is performed to room temperature;
[0091] (4) The mechanical properties of the alloys before and after hot extrusion were tested. The optimal composition was selected based on strength and elongation as Mg-7wt.%Al 10 Ca 20 Mn 20 Zn 20 Li 30 .
Claims
1. A light alloy design method with complex component synergy, characterized in that: The following steps are involved: Step 1: Preliminary Design S1: Select the target alloying elements according to the performance requirements of the light alloy to be designed, and the number of target alloying elements is ≥4; S2: The selected target alloying elements are mixed according to the thermodynamic system mixing entropy value. Combining alloying elements according to the ratio principle of medium entropy alloy and high entropy alloy greater than or equal to 1R, and obtaining the alloying element combination that meets the ratio principle of medium entropy alloy and high entropy alloy; in, , is the mixing entropy value, in J / (k·mol), R is the gas constant (=8.314 J / (k·mol)), n is the number of elements, is the atomic percentage of the corresponding element; S3: Adding alloying elements that meet the ratio principle of medium-entropy alloy and high-entropy alloy to the base material in increasing amounts to obtain a light alloy with multiple groups of complex components that are preliminarily designed to work together; Step 2: Preparation According to the elements and element contents in the light alloy of the complex components synergistically designed in the above-mentioned multiple groups, the raw materials are weighed, smelted and cast to obtain alloy ingots; The matrix material is first added during smelting, and then the alloying element combination that conforms to the ratio principle of medium entropy alloy and high entropy alloy is added. According to the state of the alloying elements after the previous combination, the addition is divided into two ways: The first method is to prepare an ingot with a combination of alloying elements that conforms to the ratio principle of medium-entropy alloy and high-entropy alloy, and then add the ingot to the matrix material in increasing amounts; The second method is to directly add the designed element components into the base material in the form of an intermediate alloy or pure metal according to the mass percentage of each element, and adjust the addition temperature and addition order according to the melting point of the alloy element; Step 3: Testing The alloy ingots or deformed samples are subjected to mechanical property tests, and the final mechanical properties of light alloys with synergistic effects of multiple groups of initially designed complex components are compared to obtain the light alloy component combination corresponding to the optimal performance.
2. The light alloy design method with complex component synergy according to claim 1 is characterized in that: In the step three, the deformed sample is obtained by hot extrusion deformation of the alloy ingot.
3. The light alloy design method with complex component synergy according to claim 2 is characterized in that: The temperature of hot extrusion deformation is 200~400℃, and the extrusion speed of hot extrusion deformation is 0.1~5 mm / s.
4. The light alloy design method with complex component synergy according to claim 1 or 2, characterized in that: The proportioning principle of medium entropy alloy is: ; The principle of high entropy alloy ratio is: >1.5R; In the alloying element combination that complies with the ratio principle of medium entropy alloy and high entropy alloy, the atomic percentage range of each alloying element is 5-35%.
5. The light alloy design method with complex component synergy according to claim 1 or 2, characterized in that: The matrix material is aluminum or magnesium.
6. The light alloy design method with complex component synergy according to claim 1 or 2, characterized in that: In the step 2, the raw materials need to be dried before smelting, the drying temperature is 100-200°C, and the drying time is 30-60 minutes.
7. The light alloy design method with complex component synergy according to claim 1 or 2, characterized in that: The smelting temperature is the temperature of the matrix ingot melting point + (50-80)°C.
8. The light alloy design method with complex component synergy according to claim 1 or 2, characterized in that: In the step 2, during smelting and casting, slag removal, refining, slag-metal separation, casting and homogenization heat treatment processes are also required.
9. The light alloy design method with complex component synergy according to claim 8, characterized in that: Specifically, the slag on the surface of the melt is removed, and the refining agent is added while stirring for 5 to 10 minutes; then the melt is allowed to stand for 15 to 30 minutes to allow the impurities and the alloy melt to be fully separated; When the alloy melt temperature is 50-80℃ above the melting point, remove the slag on the melt surface and cast it into the mold. After cooling to room temperature, take out the ingot. Inert gas is used for protection during the casting process. The homogenization heat treatment is carried out at 350-550° C. for 8-24 hours.
Citation Information
Patent Citations
Lightweight high-entropy alloy with tetragonal crystal system structure and preparation method thereof
CN104611604A
Nitrogen-strengthened TiZrHfNb-based high-entropy alloy and preparation method thereof
CN105671392A